Therapeutic implications of improved molecular diagnostics for rare CNS embryonal tumor entities: results of an international, retrospective study. Issue 9 (2nd June 2021) - von Hoff, Katja; Haberler, Christine; Schmitt-Hoffner, Felix; Schepke, Elizabeth; de Rojas, Teresa; Jacobs, Sandra; Zapotocky, Michal; Sumerauer, David; Perek-Polnik, Marta; Dufour, Christelle; van Vuurden, Dannis; Slavc, Irene; et al.
Abstract: Background: Only few data are available on treatment-associated behavior of distinct rare CNS embryonal tumor entities previously treated as "CNS-primitive neuroectodermal tumors" (CNS-PNET). Respective data on specific entities, including CNS neuroblastoma, FOXR2 activated (CNS NB- FOXR2 ), and embryonal tumors with multilayered rosettes (ETMR) are needed for development of differentiated treatment strategies. Methods: Within this retrospective, international study, tumor samples of clinically well-annotated patients with the original diagnosis of CNS-PNET were analyzed using DNA methylation arrays (n = 307). Additional cases (n = 66) with DNA methylation pattern of CNS NB- FOXR2 were included irrespective of initial histological diagnosis. Pooled clinical data (n = 292) were descriptively analyzed. Results: DNA methylation profiling of "CNS-PNET" classified 58 (19%) cases as ETMR, 57 (19%) as high-grade glioma (HGG), 36 (12%) as CNS NB- FOXR2, and 89(29%) cases were classified into 18 other entities. Sixty-seven (22%) cases did not show DNA methylation patterns similar to established CNS tumor reference classes. Best treatment results were achieved for CNS NB- FOXR2 patients (5-year PFS: 63% ± 7%, OS: 85% ± 5%, n = 63), with 35/42 progression-free survivors after upfront craniospinal irradiation (CSI) and chemotherapy. The worst outcome was seen for ETMR and HGG patients with 5-year PFS of 18% ± 6% and 22% ± 7%, and 5-year OS of 24% ± 6% and 25% ± 7%, respectively. Conclusion: The historically reported poor outcome of CNS-PNET patients becomes highly variable when tumors are molecularly classified based on DNA methylation profiling. Patients with CNS NB- FOXR2 responded well to current treatments and a standard-risk CSI-based regimen may be prospectively evaluated. The poor outcome of ETMR across applied treatment strategies substantiates the necessity for evaluation of novel treatments.